Economic gains from publicly provided education in Germany - Joachim R. Frick; Markus M. Grabka; Olaf Groh-Samberg (Institute for the Study of Labor (IZA), 2007)
The aim of this paper is to estimate income advantages arising from publicly provided education and to analyse their impact on the income distribution in Germany. Using representative micro-data from the SOEP and considering regional and education-specific variation, from a cross-sectional perspective the overall result is the expected levelling effect. When estimating the effects of accumulated educational transfers over the life course within a regression framework, however, and controlling for selectivity of households with children as potential beneficiaries of educational transfers, we find evidence that social inequalities are increasing from an intergenerational perspective, reinforced in particular by public transfers for non-compulsory education, thus negating any social equalisation effects achieved within the compulsory education framework.
Keywords: 330; Bildungsökonomik; Öffentliche Bildungsausgaben; Einkommensverteilung; Lebensstandard; Weiterbildung; Generationenbeziehungen; Deutschland